2022
DOI: 10.3390/foods11223662
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistant E. coli in Pork and Wild Boar Meat: A Risk to Consumers

Abstract: Antimicrobial-resistant foodborne microorganisms may be transmitted from food producing animals to humans through the consumption of meat products. In this study, meat that was derived from farmed pigs and wild boars was analyzed and compared. Escherichia coli (E. coli) were isolated and tested phenotypically and genotypically for their resistance to quinolones, aminoglycosides and carbapenems. The co-presence of AMR-associated plasmid genes was also evaluated. A quinolone AMR phenotypic analysis showed 41.9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Likewise, genetic homology has been detected between bacteria infecting both food-producing animals and humans, particularly in E. coli [ 35 ]. In addition, it is important to mention that meat and meat products can be contaminated at different stages of the food chain, from the slaughterhouse during evisceration to the processing stage, as well as cross-contamination of the food environment and failure to cook meat properly [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, genetic homology has been detected between bacteria infecting both food-producing animals and humans, particularly in E. coli [ 35 ]. In addition, it is important to mention that meat and meat products can be contaminated at different stages of the food chain, from the slaughterhouse during evisceration to the processing stage, as well as cross-contamination of the food environment and failure to cook meat properly [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the consumption of meat by humans is a potential route of transmission of antimicrobial resistance, and food-producing animals have been associated as a major reservoir of resistant bacterial strains, including E. coli [ 38 , 39 ]. Unexpectedly, this study found cellular infiltrate and inflammatory cells in all collected kidneys, regardless of macroscopic differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrational antimicrobial usage in farm animals is the main factor in the development of Multidrug-resistant bacteria in meat and meat products [ 1 ]. The antimicrobial resistance phenomenon (AMR) is considered a global public health concern, leading to Multidrug-resistant bacteria that can cause life-threatening diseases [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of AMR, E. coli -type bacteria are used as sentinels in humans, as well as animals, since they can survive in a variety of conditions and rapidly acquire antimicrobial resistance that can be passed to other bacteria via plasmid mediation. Furthermore, the MDR E. coli from the meat can represent a contamination source for humans that come into direct contact with uncooked or undercooked meat [ 1 ].…”
Section: Introductionmentioning
confidence: 99%